Top Common Differentially Expressed Genes in the Epileptogenic Nucleus of Two Strains of Rodents Susceptible to Audiogenic Seizures: WAR and GASH/Sal - Damasceno, Samara; Gómez-Nieto, Ricardo; Garcia-Cairasco, Norberto; Herrero-Turrión, Manuel Javier; Marín, Faustino; Lopéz, Dolores E. (Frontiers in Neurology, 2020)
The Wistar Audiogenic Rat (WAR) and the Genetic Audiogenic Seizure Hamster from Salamanca (GASH/Sal) strains are audiogenic epilepsy models, in which seizures are triggered by acoustic stimulation. These strains were developed by selective reproduction and have a genetic background with minimal or no variation. In the current study, we evaluated the transcriptome of the inferior colliculus, the epileptogenic nucleus, of both audiogenic models, in order to get insights on common molecular aspects associated to their epileptic phenotype. Based on GASH/Sal RNA-Seq and WAR microarray data, we performed a comparative analysis that includes selection and functional annotation of differentially regulated genes in each model, transcriptional evaluation by quantitative reverse transcription PCR of genes identified in common in both transcriptomes and protein analysis by immunohistochemistry. The microarray data revealed 71 genes with differential expression in WAR and the RNA-Seq data revealed 64 genes in GASH/Sal with common genes in both models. Analysis of transcripts showed that Egr3 were overexpressed in WAR and GASH/Sal and after seizures. The Npy, Rgs2, Ttr and Abcb1a genes presented the same transcriptional profile in the WAR, being overexpressed in the naïve and stimulated WAR in relation to their controls. Npy appeared overexpressed only in the naïve GASH/Sal compared to its control, while Rgs2 and Ttr genes appeared overexpressed in naïve GASH/Sal, and overexpressed after audiogenic seizure. No statistical difference was observed in the expression of Abcb1a in the GASH/Sal model. Qualitative evaluation by immunostaining allowed us to observe a higher protein expression of NPY, RGS2 and TTR in both models, but not a differential expression after seizure. Our data suggest that WAR and GASH/Sal strains have a difference in the time for gene expression after seizure, in which GASH/Sal seems to respond more quickly. The transcriptional profile of the Npy, Rgs2 and Ttr genes in the basal state of both audiogenic models indicates an intrinsic expression already established in the strains. Thus, we believe that these genes may be causing small changes in different biological processes involved in seizure occurrence and response and indirectly contributing to the susceptibility of the WAR and GASH/Sal models to audiogenic seizures.